A statistical analysis on the Manufacture of SR Vivodent A product of Zenith Company - Bescara, Honeylet C.; Reyes, Jose Ricardo J.; Tiongson, Ciselle Myn C. (Diliman, Quezon City College of Engineering, 2001)
SR VIVODENT is an injection-molding product manufactured by Zenith Company. It is manufactured in lots composed of 24,000 pieces. Rejection of the lot is a problem of the company since a rejected lot has to be manually inspected.And this is costly to the company. Thus, decreasing if not totally eliminating rejections would be the aim of the study. To accomplish this, the main causes of rejection were identified through problem analysis. The criteria for rejection, which are the main problems, are the presence of cracks, dimension deviations falling outside the allowable range, and presence of the print defects. The causes for the presence of cracks and dimension deviations were identified using the Ishikawa Diagram. Most of these root causes involve temperature. Hence, temperature was the factor to be tested for the presence of cracks and dimension deviations. Design of Experiments was utilized to test if the factor of concern, that is temperature, against other blocking factors, such as material source, cavity, and unit used, to determine the factor(s) that is/are the significant cause(s) of the main problems. A Graeco-Latin Square Design model is adapted since it can account for the treatment (factor of concern) that is temperature and the three blocking factors. From the analysis, it was found out that temperature significantly affects the presence of cracks and the deviations of the dimensions from the allowable range. For the print defects, Runs Test of Randomness, Analysis of Variance and Duncan's Multiple Range Test were performed to determine its main cause and its specific level. Results show that the third shift 12am-8am produces the most print-defective products. Hence, recommendations are : to review the temperature range currently applied, improve supervision on the third shift, 12 am-8am and to provide strict supervision and error prevention measures so as to avoid costly human errors in inputting temperature ranges on the machine units. For a more reliable result, it is recommended to consider all the factors affecting dimensions : pressure, viscosity and temperature. With a more complete data, a 2 design may be used to test the significance of the factors.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 28 : Statistical Analysis for Industrial Engineering
Keywords: Statistics